Mortality and Severity of COVID-19 Patients with Chronic Obstructive Pulmonary Disease: A Meta-Analysis - Atika Mima Amalin; Setyo Sri Rahardjo; Hanung Prasetya (Masters Program in Public Health, 2021)
Background: COVID-19 has become a pandemic in all countries including Indonesia. The death rate from COVID-19 is concentrated in elderly patients and those with comorbidities. COPD is one of the comorbidities that can worsen and even cause death. COPD ranks in the top 3 leading causes of death in the world causing 2.3 million deaths in 2019. This study aims to analyze the effect of COPD comorbidities on mortality and severity of COVID-19 patients.Subjects and Method: This study used a systematic review and meta-analysis by following the PRISMA flow chart. Search articles through journal databases, namely: Google scholar, PubMed, Science Direct and Link Springer. The articles search was done by considering the eligibility criteria defined in the PICO model. P= COVID-19 patient; I= COPD participant; C= without COPD; O= need for mechanical ventilation, ICU admission, and death. Inclusion criteria were cohort full paper articles, in English, multivariate analysis with adjusted Odds Ratio. Articles analyzed with RevMan 5.3.Results: The 13 cohort study designs reviewed with a meta-analysis to estimate the risk of death showed that comorbid COPD increased the risk of death (aOR= 1.33; 95% CI= 1.08 to 1.64; p= 0.007). 9 cohort study designs were reviewed with a meta-analysis to estimate the risk of severity with indicators of mechanical ventilation need (aOR= 1.38; 95% CI= 1.05 to 1.82; p= 0.020). 7 cohort study designs were reviewed by meta-analysis to estimate the risk of severity with indicators of risk of ICU admission (aOR= 1.25; 95% CI= 1.04 to 1.50; p= 0.020).Conclusion: COPD comorbidities increase the risk of need for mechanical ventilation, ICU admission and death among COVID-19 patients.Keywords: COVID-19, COPD, death, severityCorrespondence: